Analisis Perubahan Pendapatan Petani pada Masa Replanting Kelapa Sawit - Aldieyansah, Ilfan; Sudrajat, Jajat; Fitrianti, Wanti (Universitas Galuh, 2026)
This study aims to analyze the changes in income experienced by farmers in Parindu District due to their oil palm plantations entering the replanting phase. During this phase, oil palm production ceases for approximately 3 to 4 years, resulting in a temporary interruption in income from the commodity. This study used a descriptive method with quantitative and qualitative approaches to answer the predetermined research questions. Data were collected from primary and secondary sources, with a sample size of 68 oil palm farmers. The research findings indicate that before replanting, farmers relied heavily on oil palm plantations as their primary source of income. However, when replanting begins, income from this sector is no longer available, forcing farmers to seek alternative sources of income through non-oil palm on-farm, off-farm, and non-farm activities. Furthermore, farmers need to design appropriate financial strategies to meet their needs and cover household expenses during the replanting period.